Asparaginase-induced pseudohyponatremia, a case-driven working strategy in pediatric patients. Issue 5 (3rd September 2022) - Evenepoel, A.; Herroelen, P.; Lanckmans, K.; van der Werff Ten Bosch, J.; Martin, M.; Weets, I.; van Dalem, A.
ABSTRACT: Objectives: When using indirect ion-selective electrode (ISE) methods, hypertriglyceridemia leads to pseudohyponatremia due to water displacement artifacts. Multiple strategies exist to minimize this interference. Our objective was to create a patient-friendly one-tube-fits-all testing setup without compromising the method robustness. Methods: Four strategies were evaluated in a single patient with hypertriglyceridemia. Additionally, the interchangeability between the Cobas 8000 and ABL Flex was evaluated on samples (n = 2274) with different total protein (TP) concentrations. Finally, a proof-of-concept (n = 40) was performed by re-measuring the routine sample with the ABL90 Flex. Results: ABL90 flex results and calculated sodium did not suffer from the presence of high triglyceride levels. We did not observe any significant differences between the three groups (P > 0.05) of sample types (arterial vs. venous plasma vs. venous whole blood after mixing up) nor for the analysers (Roche vs. ABL90 Flex). Passing–Bablok and Bland–Altman tests revealed interchangeability. Conclusion: In future cases of hypertriglyceridemia, 1500 mg/dL will be used as a preliminary threshold for reliable sodium determination. Routine Li-heparin samples can be used for accurate sodium determination without any need for extra arterial or venous blood gas tubes, offering a patient-friendly test setup for similar cases.